(Almost) Square with the World - Donald J. Watts; Carol Martin Watts (Oz, 1990)
Memories of two traditions, both emphasizing being "square with the world," are embedded in our own house in Manhattan, Kansas, finished in the spring of 1989. The most immediate tradition is that of the Midwest foursquare farmhouse...